Widely targeted metabolomics analysis reveals the formation of nonvolatile flavor qualities during oolong tea manufacturing: a case study of Jinguanyin - Hu, Qingcai; Zheng, Yucheng; Yang, Yun; Ni, Zi-Xin; Chen, Bin; Wu, Zongjie; Huang, Huiqing; Wu, Qingyang; Zhou, Zi-wei; Gao, Shuilian; Lai, Zhongxiong; Lin, Hongzheng; et al. (Frontiers in Nutrition, 2023)
Background The manufacturing processes of oolong tea significantly impact its nonvolatile components, leading to the emergence of distinct flavor attributes. Understanding the dynamic changes in nonvolatile components during the manufacturing stages of the Jinguanyin (JGY) cultivar is crucial for unraveling the potential mechanism behind flavor formation. Methods Comprehensive metabolomics and sensomics analyses were conducted to investigate the dynamic changes in nonvolatile components throughout various phases of oolong tea processing, focusing on the JGY cultivar. Results A total of 1,005 nonvolatile metabolites were detected, with 562 recognized as significant differential metabolites during various phases of oolong tea processing. Notably, the third turning-over, third setting, and high-temperature treatments exhibited the most significant effects on the nonvolatile metabolites of oolong tea. JGY finished tea demonstrated a characteristic flavor profile, marked by mellowness, sweetness in aftertaste, and a significant Yin rhyme. This flavor profile was collectively promoted by the accumulation of amino acids and organic acids, the decrease in flavonols (3-O-glycosides) and sugar substances, the alteration of phenolic acids, and the stabilization of caffeine. Conclusion This study contribute to the understanding of the formation of oolong tea flavor qualities. The dynamic changes observed in various types of nonvolatile compounds during oolong tea processing shed light on the intricate interplay of metabolites and their influence on the final flavor characteristics.